Determination of Compliance of Pottery MSME Taxpayers in Kasongan Tourism Village - Subowo, Farida; Utomo, Rochmad Bayu (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study aims to determine the positive influence of Tax Socialization and Tax Authority Trust on Taxpayer Compliance mediated by Tax Payment Intention. This study discusses how Pottery MSMEs are tax-compliant. This research is quantitative because it uses numerical data processing. The subject of the study is 60 Pottery MSMEs with Tax Payer ID Number and banking credit above IDR 50 million with a business establishment period of more than 1 year. The sampling technique uses purposive sampling. Research uses descriptive and quantitative analysis methods with Structural Equation Modelling (SEM) approach mainly utilizing Partial Least Squares (PLS). The results of the study showed that Tax Socialization and Trust in Tax Authority had a positive effect on Tax Payment Intention, Tax Payment Intention had a positive impact on Taxpayer Compliance, and Tax Socialization and Trust in Tax Authority had a positive indirect influence through Intention to Pay Tax of Pottery MSME in Kasongan Tourism Village.